Teacher's TPK Creativity: Canva-Based Student Worksheet (LKPD) Innovation to Enhance Learning Motivation - Rinna Hidayati; Syamsudin Syamsudin (International Journal of Education, Vocational and Social Science, 2026)
The main objective of this research is to describe the Technological Pedagogical Knowledge (TPK) creativity of 1st-grade teachers in developing Canva-based Student Worksheets (LKPD), analyze its implications on students' learning motivation, and identify the supporting and inhibiting factors at MI Al Fithrah Surabaya. This research uses a descriptive qualitative method. The researcher acts as the main instrument with data collection techniques in the form of observation, in-depth interviews with 1st-grade teachers, and documentation of LKPD drafts. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and drawing conclusions, with validity testing through source and technique triangulation. The research results show that teachers successfully implemented TPK creatively through independent layout modifications, the integration of child-friendly graphic elements, and bright color combinations without relying entirely on instant templates. The application of this LKPD is proven to have a significant positive impact on learning motivation, as indicated by increased cheerfulness, longer attention spans, and a more orderly classroom atmosphere. The main supporting factor includes adequate facilities. In conclusion, the teachers' TPK creativity in designing LKPD is proven to be effective in overcoming the short attention spans of lower-grade students. Teachers are advised to consistently utilize this visual media to maintain the quality of learning.